PENGARUH TOTAL ASSET TURNOVER, DEBT TO EQUITY RATIO, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Suci Faradila; Lita Permata Sari; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine and analyze the influence of Total Asset Turnover, Debt to Equity Ratio, and Sales Growth on Firm Value, with Profitability serving as an intervening variable. The research focuses on manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employed a quantitative research approach using the Partial Least Squares (PLS) method with the assistance of SmartPLS 3.0 software for data analysis. The analytical procedures included classical assumption testing, such as normality and multicollinearity tests, coefficient of determination analysis, structural model (inner model) evaluation, and hypothesis testing to assess both direct and indirect relationships among variables. The findings reveal that Total Asset Turnover exerts a negative but insignificant effect on Profitability, while Debt to Equity Ratio demonstrates a negative and significant effect on Profitability. In contrast, Sales Growth has a positive and significant effect on Profitability. Furthermore, Total Asset Turnover and Debt to Equity Ratio do not significantly influence Firm Value, whereas Sales Growth and Profitability positively and significantly affect Firm Value. The study also indicates that Profitability is unable to mediate the relationship between Total Asset Turnover, Debt to Equity Ratio, and Sales Growth on Firm Value.